Approximations to Landau’s problems on prime numbers - Merikoski, Jori (fi=Turun yliopisto|en=University of Turku|, 2021)
In this thesis we study the distribution of prime numbers by considering approximations to fundamental open conjectures about them. The conjectures in question are the so-called Landau’s problems, named after Edmund Landau who in 1912 listed four basic questions about prime numbers at the International Congress of Mathematicians. All of the four problems remain unsolved and are widely considered to be beyond the reach of current mathematics. To study prime numbers we use sieve methods to break the problem into parts that can be attacked with various analytical tools. Sieves can be viewed as combinatorial machines that take as inputs arithmetic information about a given set and produce as outputs lower and upper bounds for the number of primes or almost-primes in the set. The thesis consists of four articles. In the first article we consider the problem of showing that all short intervals contain numbers with large prime factors. We use Harman’s sieve method and Perron’s formula to reduce the problem to certain mean value estimates for Dirichlet polynomials. We obtain a suitable factorization for these Dirichlet polynomials by using a much refined version of the argument of Heath-Brown and Jia from their work on the same problem. After this the Dirichlet polynomial mean values can be bounded by applying the method of Matomäki and Radziwiłł. In the second article we study the set of limit points of the sequence of normalized prime gaps. Improving on previous results of Baker, Banks, Freiberg, Maynard, and Pintz, we show that at least one third of non-negative real numbers are limit points of the sequence of normalized prime gaps. To attack this problem we combine the Maynard-Tao sieve with Chen’s sieve. In the third and the fourth articles we consider two different approximations to the conjecture that there are infinitely many primes of the form n2 + 1. In the third article we study the largest square divisor of shifted primes and in the fourth article we study the largest prime factor of n2 + 1. In both cases we apply Harman’s sieve method. The arithmetic information in the third and the fourth articles is obtained by a square moduli version of Zhang’s bilinear equidistribution estimate and by the Deshouillers-Iwaniec bound for sums of Kloosterman sums, respectively. The third article improves the results of Matomäki, while the fourth article improves the results of Deshouillers and Iwaniec, and de la Bretèche and Drappeau.

Tässä väitöskirjassa tutkimme alkulukujen jakaumaa tarkastelemalla aproksimaatiota niitä koskeviin keskeisiin avoimiin konjektuureihin. Nämä konjektuurit tunnetaan nimellä Landaun ongelmat. Tämä nimi tulee Edmund Landausta, joka vuonna 1912 kongressissa International Congress of Mathematicians nosti esiin neljä keskeistä ongelmaa alkulukuja koskien. Kaikki neljä ongelmaa ovat edelleen ratkaisematta ja niiden ajatellaan yleisesti olevan tämänhetkisen matematiikan ulottumattomissa. Tutkiaksemme alkulukuja käytämme seulamenetelmiä paloittelemaan ongelman osiin, joita voimme tarkastella käyttäen erilaisia analyyttisiä menetelmiä. Seuloja voidaan pitää kombinatorisina koneina, joihin syötetään aritmeettista informaatiota annetusta joukosta ja jotka tuottavat ala- ja ylärajoja kyseisessä joukossa olevien alkulukujen tai melkein-alkulukujen lukumäärälle. Tämä väitöskirja koostuu neljästä artikkelista. Ensimmäisessä artikkelissa osoitamme, että kaikilta lyhyiltä väleiltä löytyy luku, jolla on suuri alkutekijä. Käytämme Harmanin seulamenetelmää ja Perronin kaavaa palauttamaan ongelman tiettyihin Dirichlet’n polynomien keskiarvohin. Osoitamme näille Dirichlet’n polynomeille tarvittavan tekijöihinjaon käyttäen paljon tarkennetua versiota Heath-Brownin ja Jian argumentista koskien samaa onglemaa. Tätä hyödyntäen pystymme osoittamaan näille Dirichet’n polynomien keskiarvoille ylärajan käyttäen Matomäen-Radziwiłłin menetelmää. Toisessa artikkelissa tutkimme normalisoitujen alkulukujen etäisyyksien jonon kasautumispisteiden joukkoa. Osoitamme, että ainakin yksi kolmasosa kaikista einegatiivisista reaaliluvuista ovat normalisoitujen alkulukujen etäisyyksien jonon kasautumispisteitä, mikä parantaa Bakerin, Banksin, Freibergin, Maynardin, ja Pintzin aiempia tuloksia. Ongelman tutkimiseen käytämme yhdistelmää Maynardin-Taon seulasta ja Chenin seulasta. Kolmannessa ja neljännessä artikkelissa tarkastelemme kahta eri aproksimaatiota konjektuuriin, jonka mukaan on olemassa äärettömän paljon muotoa n2 + 1 olevia alkulukuja. Kolmannessa artikkelissa tutkimme alkulukujen siirtojen suurinta neliötekijää ja neljännessä artikkelissa tutkimme lukujen n2 + 1 suurimpia alkutekijöitä. Kolmas artikkeli parantaa Matomäen tulosta, kun taas neljäs artikkeli parantaa Deshouillersin-Iwaniecin ja de la Bretèchen-Drappeaun tulosta. Molemmissa tapauksissa käytämme Harmanin seulamenetelmää. Aritmeettinen informaatio saadaan kolmannessa artikkelissa neliömoduli-versiosta Zhangin bilineaarisesta tasanjakautumisarviosta ja neljännessä artikkelissa Deshouillersin-Iwaniecin arvioista summille Kloostermanin summista.